USE OF CIPC (ISOPROPYL N-(3-CHLOROPHENYL) CARBAMATE) FOR THE CONTROL OF POTATO TUBER MOTH IN COUNTRY STORES - Chandel, R. S.; Singh, Brajesh; Chandla, V. K.; Sharma, P. K. (Potato Journal, 2013)
Investigations on the management of Phthorimaea operculella (Zeller) using CIPC (isopropyl N-(3-chlorophenyl) carbamate) revealed that it holds considerable potential to control P. operculella in stored potatoes meant for table and processing purposes. Spray of commercial formulation of CIPC (30% EC) @ 60ml / 140ml of water per tonne of potato, reduced infestation to negligible. After 50 days of storage, there was 80-84 percent reduction in pest infestation with CIPC treatment. In CIPC treated tubers, the damage was only superficial, the tuber skin was firm and the tubers were in perfect shape without any sprouts. There was almost 95 percent sprout inhibition in treated tubers. The residues were quite low (0.24-0.87 mg / kg f. wt.) in peeled tubers collected immediately after spray and these were well below the permissible limits defined for CIPC by Environmental Protection Agency. CIPC treatment assures greater sustainability, as it is neither costly, nor labour intensive.